Optimization of granularity aggregate of the periclase concrete - Пісчанська, Вікторія Вікторівна; Алєксєєнко, Інна Анатоліївна (Technology audit and production reserves, 2015)
Magnesia concrete used for the manufacture of complex configuration and monolithic linings of thermal units of ferrous and nonferrous metallurgy, industry of cement production is effective respond to combination of high temperature properties and adaptive capacity to the conditions of usage. Promising species of magnesia concrete include periclase concrete on hydraulic binders such as concretes containing cements of different nature. Using simplex-lattice method of planning experiment it is investigated the influence of grain size of concrete mixes, which contain a filler recycled materials – crushed lack of periclase products and sintered periclase, and a binder – a mixture of periclase and calcium-alumina cements on the performance properties of the treated periclase concrete. Using the obtained polynomial models in the "structure-property" optimized particle size distribution of periclase concrete on hydraulic binders, which corresponds to a ratio of narrow fractions of filler and achieves a complex set of physical and technical properties of the composite indexes after drying and high-temperature firing.